Choosing optimal combination of neuro-humoral modulators in chronic heart failure: CHARM-Added study lessons - Yu. M. Lopatin (Кардиоваскулярная терапия и профилактика, 2007)
The article is focused on choosing optimal doses and combinations of neuro-humoral modulators in systolic left ventricular dysfunction and heart failure. The results of CHARM-Added, Val-HeFT, RALES, and EPHESUS studies are analyzed, as well as their effect on modern recommendations on chronic heart failure diagnostics and treatment.